REELABORATIONS AND PARTICULARIZATIONS: NOTES ON DOM BOSCO'S EDUCATIONAL EXPERIENCES GROUNDED ON VITORINO DA FELTRE AND FELIPE NERY. (Fiep Bulletin - online, 2014)
This paper refers to a part of a concluded study and in the present section I specifically approach one of Lê Goff's postulates. According to this author, it is possible that determined phenomena or facts occurred in a given period may be characterized as modernisms of previous occurrences. In this manner, studying a traditional proposition for education - the Salesians', implemented by the Italian priest and educator John Bosco (Don Bosco) during the 18 hundreds - I was able to perceive evidence indicating many similarities between this proposition's original pedagogic elements and others occurred during the XV and XVI centuries with Vitorino da Feltre and Felipe Neri, respectively. The few records available on the works developed by Vitorino in a place called Casa Giocosa, as well as the non-abundant records on Felipe's works initiated in a place called Oratório de São Girolamo da Caridade allowed me to find pedagogic elements and characteristics common to both experiences, despite Vitorino's lay character and the strict religiosity in Felipe's works. Among these characteristic elements, I will focus on a special one - the joy - for this element appeared in a prominently positive way in Bosco's experience in the Oratório de São Francisco de Sales. The argumentation was built from the presentation of various primary and secondary sources in Salesian tradition. But the main source was a document named Panegírico de São Felipe Neri, written by Don Bosco himself. It is the source analysys, of the Panegírico (Eulogy) mainly, that allowed the necessary argumentations to sustain the hypothesis and led to favorable my final comments corroborating the hypothesis.
Keywords: Joy; Education; History